Monthly 24-hour water parameter measurements from a Raspberry-based controller during a multi-stressor aquarium experiment - Cristina Gutiérrez-Zárate; Alfredo Veiga; Andrea Gori; Fabián Gerpe; Leo Domínguez; Alberto Rodríguez; Noelia Arias; Marta Álvarez; Rubén Acerbi; Lucía Vázquez; Juancho Movilla; Marta M Varela; et al. (PANGAEA, 2024)
A 9-month aquarium experiment with the cold-water Dendrophyllia cornigera was conducted to investigate the single and combined effects of warming, acidification and deoxygenation on its ecophysiological response. The experiment took place at the Aquarium finisterrae (A Coruña, Spain) between 2022-05-06 and 2023-02-24. Treatment values for each parameter (current in situ vs. climate change) were: 12 °C and 15 °C (temperature); ~7.99 and 7.69 (pH); ~8.63 mg/L and 6.45 mg/L (dissolved oxygen concentration). A total of eight treatments (with 3 replicates each, 5 L aquaria) were set up. Raspberry-based controllers were set to modify and monitor the water temperature, pH and dissolved oxygen in every treatment. Values for temperature (C), pH (NBS scale) and oxygen (% saturation) were registered every 15 minutes in a database. The parameters were measured using ds18b20 temperature sensors, and Atlas Scientific lab grade pH and dissolved oxygen sensors. Every set of sensors was placed on each header tank, corresponding to each treatment (8 in total). Parameter setpoint values for each header tank were finely adjusted on the controller to ensure the treatment target values on each experimental aquaria. Oxygen sensors from treatments with ambient oxygen (~8.63 mg/L) were removed from the system due to calibration issues. Here, a monthly sample of the results for temperature, pH and oxygen for every header tank over 24 hours from June 2022 to February 2023 is presented. Values for pH (total scale) and dissolved oxygen (mg/L) were calculated using AquaEnv (Hofmann et al. 2010) and respR (Harianto et al. 2019) R packages, respectively, using the in situ temperature and salinity. Dissolved oxygen concentrations in treatment tanks under ambient oxygen conditions were obtained using independent measurements taken the same day with a YSI ProODO dissolved oxygen instrument.